LED 광 조사와 백급 추출물이 멜라닌 형성 억제에 미치는 영향 - 김서진; 주시유; 김옥준; Seojin Kim; Siyu Zhu; Okjoon Kim (대한구강악안면병리학회지, 2025)
Skin color is primarily determined by the amount of melanin pigmentation in the skin. In recent years, cosmetic compositions have been developed to reduce the melanin pigmentation in the skin. Treatment of the skin with whitening agents, from the pharmacological and cosmetological views, should provide safety and efficacy without side effects. Currently used whitening agents which are mostly cause many harmful and cytotoxic effects. In view of the lack of safe whitening agents, this study has been conducted to find the stable and harmless compounds inhibiting melanogenesis. The use of light and Herbal extract for the purpose of skin whitening has been formally reported. So, this study is to investigate the effects of LED irradiation and Bletillae rhizoma (Br) extract on tyrosinase activity and melanin biosynthesis in B16F0 melanoma cells. Melanin biosynthesis was induced by α-MSH. Experimental group were conducted five groups; 1) Pre-LED group (LED light irradiation, followed by 1 μM α-MSH) 2) Post-LED group (α-MSH treat, followed by LED light irradiation) 3) Pre-Br extract group (Br extract treat, followed by 1 μM α-MSH) 4) Post-Br extract group (α-MSH treat, followed by 10 μg/ml Br extract) 5) LED and Br extract group. The melanin contents, tyrosinase activity, dendrite length of cells and expression of melanogenesis-related genes under LED light irradiation and Br extract treatment were investigated. Pre-635, Post-425 nm and Post-Br extract group were significantly reduced melanin contents and tyrosinase activity compared with other group. But both for LED irradiation and Br extract group, melanin contents and tyrosinase activity were increased. However, Pre-425 nm and Post-Br extract group could reduce the melanin contents, tyrosinase activity and dendrites length of cells. In addition, the expression of melanogenesis-related proteins, including microphthalmia associated transcription factor (MITF) and tyrosinase (TYR) is inhibited. The Pre-425 nm and Post-Br extract group activated Extracellular signal-regulated kinase (ERK) phosphorylation and involved in the inhibition of melanogenesis via stimulation of MITF degradation. These results indicate that the inhibitory effect of Pre-425nm irradiation and Post-Br extract on melanogenesis are derived from reduced TYR expression via the downregulation of MITF signaling, as well as acceleration of ERK phosphorylation. Thus, these results suggest that Pre-425nm irradiation and Post-Br extract could prevent and treat melanin hyperpigmentation or useful in whitening agents.